(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the relevance of developing color skills in the process of professional training of future architects. The role of colors in architectural design, their impact on human psychology, color harmony and composition, as well as ways to increase efficiency in working with colors using modern information technologies are discussed. The article recommends methods that encourage students to think creatively through practical exercises, project-based learning, and the use of innovative methods. The role of color knowledge in the formation of the aesthetic taste of future architects is shown on the basis of experience.